Data-centric routing and caching approach for mobile and social sensing applications. (September 2021) - Shynu, P.G.; Al-Turjman, Fadi
Highlights: Providing efficient routing and content management for ICN. It enables bandwidth and cost-based routing for mobile and social sensing applications. Caching is an important feature of ICN. Cache replacement policy proposed to improve ICN performance. Abstract: Information-Centric Network (ICN) is an essential networking model which contains several future Internet research activities. This paper considers ICN architecture for mobile and social sensing data. Routing and caching are among the most critical features of ICN, which improves the performance of efficiency of network and content sharing by fulfilling user requirements with cached content. This paper introduces a new routing model for information-centric network based on least bandwidth and cost (LBC) with two cache replacement policies. The cache replacement policies find and replace the content in the free cache space. Time aware Least Recently Used (TLRU) and Least Frequent Recently Used (LFRU) are employed as a cache replacement policy. The proposed algorithm implemented and compared, with the previous algorithm in terms of the following metrics success rate, hop count and delay. The results of the experiments show that the proposed algorithm is more effective compared to other algorithms. Graphical abstract: Image, graphical abstract